2007
DOI: 10.1002/asi.20779
|View full text |Cite
|
Sign up to set email alerts
|

Wisecrackers: A theory‐grounded investigation of phishing and pretext social engineering threats to information security

Abstract: The collection and dissemination of information about people by businesses and governments is ubiquitous. One of the main threats to people's privacy comes from human carelessness with this information, yet little empirical research has studied behaviors associated with information carelessness and the ways that people exploit this vulnerability. The studies that have investigated this important question have not been grounded in theory. In particular, the extant literature reveals little about social engineer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 77 publications
(124 reference statements)
8
143
0
4
Order By: Relevance
“…In this respect, the related work on user susceptibility to phishing and other semantic social engineering attacks is highly relevant. Predicting whether a user will be deceived into clicking on a fraudulent link or not has traditionally been studied in the realm of behavioural science, where different studies have found that higher degrees of normative, affective and continuance commitment, obedience to authority and trust (M. Workman, 2008), submissiveness (I. M. A. Alseadon, 2014), neurotic behaviour (T. Halevi, 2013) and conscientiousness (T. Halevi et al, 2015) all correlate with high susceptibility to phishing.…”
Section: Related Workmentioning
confidence: 99%
“…In this respect, the related work on user susceptibility to phishing and other semantic social engineering attacks is highly relevant. Predicting whether a user will be deceived into clicking on a fraudulent link or not has traditionally been studied in the realm of behavioural science, where different studies have found that higher degrees of normative, affective and continuance commitment, obedience to authority and trust (M. Workman, 2008), submissiveness (I. M. A. Alseadon, 2014), neurotic behaviour (T. Halevi, 2013) and conscientiousness (T. Halevi et al, 2015) all correlate with high susceptibility to phishing.…”
Section: Related Workmentioning
confidence: 99%
“…The social engineer will determine which tactic would be most suitable and successful for tricking the victim. This task also involves developing a good plan to reach that goal, which can include "pretexting," in which a social engineer creates a setting designed to persuade the victim to fall for the trick [35]. It also involves determining which steps and phases should be taken to reach the goal, and determining the best time to launch each step.…”
Section: B the Ability To Develop A Planmentioning
confidence: 99%
“…Agindo dessa maneira todos são beneficiados, uma vez que da parte dos colaboradores haverá o compromisso com a proteção das informações sensíveis da organização; e da parte da organização haverá esforços para fornecer algum tipo de proteção (WORKMANN, 2007).…”
Section: Segurança Da Informação E Gestão De Pessoas: Um Processo De unclassified
“…Conforme Workmann (2007), quando ocorre internamente o ato de percepção, as ações e reações podem ser alteradas e nesse caso o instrumento promotor da mudança é a comunicação persuasiva. Por isso mesmo, o fator persuasão é determinante do comportamento das pessoas frente a situações de ameaça.…”
Section: Veiga; Eloff 2009)unclassified
See 1 more Smart Citation